Preferences for Supplier Evaluation Criteria at the Aspect of Digital Transformation of Purchasing Process – Manager’s Point of View - Lukasz HADAS; Katarzyna RAGIN-SKORECKA (Communications of International Proceedings, 2021)
Aim: The main aim of the research was to identify the supplier assessment practice and the preferences of managers in the context of digital transformation of purchasing processes. The research problem concerns the identification of supplier evaluation criteria in the enterprises and what is their rank. Methodology: The results of the study was a part of a broader research on the organization of purchasing processes. The research process includes two following general steps: preparation of a questionnaire and CATI  (101 respondents) research and in-depth interview with experts with experience in purchasing (implementation of purchasing processes, including the selection and evaluation of suppliers). Findings: The obtained research results allowed to determine what are the currently used supplier evaluation criteria in the surveyed enterprises and what is their rank in relation to the others. Then, it was determined what are the limitations of the supplier assessment and what IT support would be useful in the opinion of managers. Conclusions: The obtained research results expanded the knowledge about the current practice of supplier assessment and the requirements formulated by managers of purchasing or logistics departments in the field of IT-supported this process. On the threshold of widespread digital transformation of purchasing processes in enterprises it is necessary to further improve the functionality related to the multi-faceted assessment of the supplier.
Keywords: Procurement; e-procurement; e-sourcing; supplier evaluation; digital transformation